Effectiveness of mindfulness meditation on psychological well-being among undergraduate nursing students in selected nursing campuses, Nepal - Pandey Bista, Archana; Tamrakar, Neeta; Adhikari , Jamuna; Kumari Sah, Bimala; Sigdel, Dipa; Pandey, Apsara (Journal of Chitwan Medical College, 2025)
Introduction: Mindfulness meditations have been effective to reduce stress and improve psychological well-being among students. Thus, this study aimed to measure the effectiveness of mindfulness meditation interventions on psychological well-being among undergraduate nursing students. Method: An experimental research design was adopted. A total of 130 students studying at two nursing campuses were randomly assigned into two groups, 65 in each: (i) Mindfulness meditation group and (ii) Waiting list control group. Ethical approval was obtained from the Nepal Health Research Council. Data were collected from Jan to Apr 2022 by using Ryff’s scales of psychological well-being. Before the intervention, pre-test was obtained from both groups. The intervention group received mindfulness meditation intervention for one week and was virtually guided for practicing for six weeks. After the intervention, post-tests were obtained from both groups. Data were analysed by using descriptive and inferential statistics such as paired t-test and independent samples t-test to measure the significant differences in subscales of psychological well-being before and after the intervention within and between groups. Result: In four subscales higher scores were observed among the experimental group than the control group, with statistically significant differences on the personal growth scale (p<0.001), purpose in life scale (p<0.001), self-acceptance scale (p<0.001), positive relations with others (p<0.003), and environmental mastery (p<0.080) with effect sizes ranging from 0.54 to 0.80. No statistical association was observed on the autonomy scale (p=0.361). Conclusion: A six-week mindfulness meditation intervention has positive effects on increasing most aspects of psychological well-being among undergraduate nursing students.